2015
DOI: 10.3917/ag.702.0300
|View full text |Cite
|
Sign up to set email alerts
|

La prison, la police et le quartier. Gouvernement urbain et illégalismes populaires à Yaoundé

Abstract: International audienceCet article a pour objectif de discuter de la place de la prison dans les rapports sociaux et de pouvoir en ville, depuis l’Afrique, plus exactement depuis Yaoundé, la capitale politique du Cameroun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
1
0
4
Order By: Relevance
“…There is also scholarship of overlaps and synergies between spaces. In particular, Loyd et al (2013) and Morelle (2015) have influentially demonstrated interactions between prisons, migration policing and detention, including in the Global South. Following Foucault's rippling carceral circles, a variety of domestic, urban, and embodied sites have been theorized as spaces of surveillance and control reminiscent of the diffuse carceral model, with carceral geographers tracing the relationships between the prison as a compact but porous carceral institution and these other spaces.…”
Section: The Development Of Carceral Geographymentioning
confidence: 99%
“…There is also scholarship of overlaps and synergies between spaces. In particular, Loyd et al (2013) and Morelle (2015) have influentially demonstrated interactions between prisons, migration policing and detention, including in the Global South. Following Foucault's rippling carceral circles, a variety of domestic, urban, and embodied sites have been theorized as spaces of surveillance and control reminiscent of the diffuse carceral model, with carceral geographers tracing the relationships between the prison as a compact but porous carceral institution and these other spaces.…”
Section: The Development Of Carceral Geographymentioning
confidence: 99%
“…e a prisão. Morelle (2015), ao discutir a construção política e social da população detida na prisão central de Yaoundé, capital camaronesa, realça os fios que unem essa prisão aos bairros populares. Waltorp e Jensen (2019), a partir de trabalho de campo em periferias da Cidade do Cabo, África do Sul, salientam como esses espaços estão atados, ainda que eles sejam descritos pelos residentes dessas áreas como pertencentes a mundos morais distintos.…”
Section: A Prisão Em Suas Correlações Com O Foraunclassified
“…A explosão da população carcerária ao longo das últimas décadas, processo que Garland (2001) chamou de encarceramento em massa, e Wacquant (2009), numa definição mais precisa, de hiperencarceramento concentrado, fomentou uma série de estudos que lançam luz sobre o imbricamento das prisões com determinadas regiões urbanas, tais como periferias e favelas brasileiras (Barbosa, 2005), guetos estadunidenses (Wacquant, 2007), townships sul-africanas (Waltorp & Jensen, 2019), banlieues parisienses (Bony, 2015) ou bairros portugueses (Cunha, 2002) e camaroneses (Morelle, 2015) específicos -em suma, as áreas habitadas pelas populações mais pobres das cidades. Entre outras potencialidades, esses escritos ressaltam a concentração espacial do encarceramento, a incorporação dos bairros pela prisão -bem como da prisão pelos bairros -e a disseminação da experiência carcerária entre esses territórios e suas populações, delineando um continuum entre prisões-favelas-periferias.…”
Section: Introductionunclassified